Predicted extracapsular invasion of hilar lymph node metastasis by fusion positron emission tomography/computed tomography in patients with lung cancer - MAKINO, TAKASHI (Mol Clin Oncol, 2015)
Intraoperative detection of hilar lymph node metastasis, particularly with extracapsular invasion, may affect the surgical procedure in patients with lung cancer, as the preoperative estimation of hilar lymph node metastasis is unsatisfactory. The aim of this study was to investigate whether fusion positron emission tomography/computed tomography (PET/CT) is able to predict extracapsular invasion of hilar lymph node metastasis. Between April, 2007 and April, 2013, 509 patients with primary lung cancer underwent surgical resection at our institution, among whom 28 patients exhibiting hilar lymph node metastasis (at stations 10 and 11) were enrolled in this study. A maximum lymph node standardized uptake value of >2.5 in PET scans was interpreted as positive. A total of 17 patients had positive preoperative PET/CT findings in their hilar lymph nodes, while the remaining 11 had negative findings. With regard to extracapsular nodal invasion, the PET/CT findings (P=0.0005) and the histological findings (squamous cell carcinoma, P=0.05) were found to be significant predictors in the univariate analysis. In the multivariate analysis, the PET/CT findings were the only independent predictor (P=0.0004). The requirement for extensive pulmonary resection (sleeve lobectomy, bilobectomy or pneumonectomy) was significantly more frequent in the patient group with positive compared with the group with negative PET/CT findings (76 vs. 9%, respectively, P=0.01). Therefore, the PET/CT findings in the hilar lymph nodes were useful for the prediction of extracapsular invasion and, consequently, for the estimation of possible extensive pulmonary resection.